Development of Hot-Mix Asphalt Layer Thickness Design for Longer-Life Asphalt Pavements - Jitsangiam, Peerapong; Nikraz, Hamid; Leek, Colin (PATREC, 2010)
Flexible pavements with thin bitumen surfacing form one of the largest infrastructure components in the Australian sealed road network and are a complex system of multiple sub-layers of different materials and combinations of variables. More effective and rational pavement analysis and design which can incorporate the performance characteristics and failure mechanisms of pavements relating to realistic conditions are needed to overcome current design shortcomings. This research project will initiate a new pavement design methodology, providing a more realistic approach for pavement design. It will bring about an advance in pavement design and analysis, and result in more effective analysis and design of pavements world-wide.